2007
DOI: 10.1128/iai.00004-07
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immune Responses to a Recombinant Adenovirus Type 35 Tuberculosis Vaccine in Two Mouse Strains: CD4 and CD8 T-Cell Epitope Mapping and Role of Gamma Interferon

Abstract: There is an urgent need for an efficacious vaccine against tuberculosis (TB). Cellular immune responses are key to an effective protective response against TB. Recombinant adenovirus (rAd) vectors are especially suited to the induction of strong T-cell immunity and thus represent promising vaccine vehicles for the prevention of TB. We have previously reported on rAd vector serotype 35, the serotype of choice due to low preexisting immunity worldwide, which expresses a unique fusion protein of Mycobacterium tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
118
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 54 publications
13
118
1
Order By: Relevance
“…In the ICS assay, the CD4 responses were relatively low compared to the CD8 responses, while by the ELISPOT assay the difference was less pronounced (data not shown), confirming a previously published observation of the high sensitivity of the ELISPOT assay relative to that of the ICS for the detection of antigen-specific CD4 responses (41).…”
Section: T-cell Epitope Mapping Upon Rad35lsa-1 Immunizationsupporting
confidence: 88%
See 3 more Smart Citations
“…In the ICS assay, the CD4 responses were relatively low compared to the CD8 responses, while by the ELISPOT assay the difference was less pronounced (data not shown), confirming a previously published observation of the high sensitivity of the ELISPOT assay relative to that of the ICS for the detection of antigen-specific CD4 responses (41).…”
Section: T-cell Epitope Mapping Upon Rad35lsa-1 Immunizationsupporting
confidence: 88%
“…A possible explanation of our results is that the LSA-1 protein expression and the antigen processing upon immunization are not optimal for the induction of T-helper cells required to trigger anti-LSA-1 antibody responses, probably due to the modified sequence of the protein (24). In line with this hypothesis, it is noteworthy that a relatively high dose of rAd35 (10 10 VP) was required to induce significant T-cell responses, in contrast to our previous results with other rAd35 vectors where a 1-log-lower dose (10 9 VP) was sufficient to induce an optimal T-cell response (37,38,41). The heterologous vaccination regimens elicited a level of anti-LSA-1 IgG responses comparable to that seen for the protein vaccinations.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…delivery (13). We found that rAd35 is highly immunogenic in the lungs when given by aerosol to rhesus macaques (Fig.…”
Section: Resultsmentioning
confidence: 79%